Exosomal miR-590-3p derived from cancer-associated fibroblasts confers radioresistance in colorectal cancer - Xijuan Chen; Yingqiang Liu; Qinglan Zhang; Baoxing Liu; Yan Cheng; Yonglei Zhang; Yanan Sun; Junqi Liu (Elsevier, 2021)
Radiotherapeutic resistance is a major obstacle for the effective treatment of colorectal cancer (CRC). MicroRNAs (miRNAs) play a critical role in chemoresistance and radioresistance. Here, we aimed to investigate whether miR-590-3p participates in the radioresistance of CRC. High expression of miR-590-3p and low expression of CLCA4 were found in both CRC tissues and cell lines. CLCA4 was indicated to be a target gene of miR-590-3p. CAF-derived exosomes were extracted and co-cultured with CRC cells, which were then exposed to radiation. CRC cells were transfected with plasmids and injected into nude mice to detect the in vivo effect of CAF-derived exosomes. Treatment with CAF-derived exosomes decreased the sensitivity of CRC cells to radiation. CAF-derived exosomes overexpressing miR-590-3p increased cell survival and the ratio of p-PI3K/PI3K and p-AKT/AKT while lowering the expressions of cleaved-PARP, cleaved-caspase 3, and γH2AX in cells. Furthermore, in vivo experimental results confirmed that CAF-derived exosomal miR-590-3p stimulated tumor growth in mice following radiotherapy. Our results demonstrate that miR-590-3p delivery via exosomes derived from CAFs enhances radioresistance in CRC through the positive regulation of the CLCA4-dependent PI3K/Akt signaling pathway.